Clinical experience in management of bloodstream infection in emergency medical ward: A preliminary report. Issue 4 (July 2021) - Cheung, Ying; Ko, Shing; Wong, Oi Fung; Lam, Hoi Shiu Bosco; Ma, Hing Man; Lit, Chau Hung Albert
Background: Bloodstream infection is a life-threatening clinical condition posing significant morbidities and mortalities. An "Emergency Critical Care Management Program" has been implemented in the Emergency Medicine Ward at North Lantau Hospital as a pilot critical care service model in the local emergency medicine wards. Patients with blood stream infection are recruited in the program and managed under pre-defined guideline. Objectives: We report our experience in managing patients with blood stream infection in the Emergency Medicine Ward and analyzed their clinical outcomes. Methods: This was a retrospective cohort study including a total of 64 patients with blood stream infection admitted to the Emergency Medicine Ward from 1 March 2015 and 31 March 2018. Patients' characteristics, microbiology, and risk factors associated with adverse outcomes including in-hospital mortality were analyzed. Results: The most common organism isolated from blood cultures was Escherichia coli (56%). Eight patients were transferred to the tertiary hospital. The overall in-hospital mortality was 7.8% (5/64). From the univariate analysis, advanced age (p < 0.001), higher Sequential Organ Failure Assessment score and quick Sequential Organ Failure Assessment score (p < 0.001), higher Charlson Comorbidity Index (p = 0.003), more organ dysfunction (p < 0.001), pre-existing medical history of chronic liver disease (p = 0.001), dysfunction in respiratory system (p = 0.032), cardiovascular system (p = 0.044) and the central nervous system (p < 0.001), presence of septic shock (p = 0.004), and need for higher level of organ support from the use of inotropes (p < 0.001) and mechanical ventilation (p = 0.024) were associated with in-hospital mortality. In the subgroup analysis, the in-hospital mortality rate for the patients with Sequential Organ Failure Assessment score less than 6 was 1.56% (1/64). Among the five in-hospital mortality cases, four of them were managed in the Emergency Medicine Ward under the End-of-Life Care Program. Decision for withholding and withdrawing life-sustaining therapy was made with the patients' families. Conclusion: This preliminary report demonstrated that with careful patient selection, adoption of guidelines, and availability of expertise, critical care service can be safely implemented in the emergency medicine ward.